Alkaline phosphatase activity in salivary gland cells of Rhodnius neglectus and R-prolixus (Hemiptera, Triatominae) - Lima-Oliveira, A. P. M. [UNESP]; Alevi, K. C. C. [UNESP]; Anhe, A. C. B.; Azeredo-Oliveira, M. T. V. [UNESP] (Funpec-editora, 2016)
Alkaline phosphatase activity was detected in salivary gland cells of the Rhodnius neglectus Lent, 1954, and R. prolixus Stal, 1859, vectors of Trypanosoma cruzi Chagas, 1909 (etiological agent of Chagas disease) and T. rangeli Tejera, 1920 (pathogenic to insect). The Gomori technique was used to demonstrate alkaline phosphatase activity. Alkaline phosphatase activity was observed throughout the entire gland, with an increased activity in the posterior region of the principal gland. In particular, phosphatase activity was found in the nucleolar corpuscles, suggesting a relationship with the rRNA transcription and ribosomal biogenesis. Alkaline phosphatase was also detected in the nuclear membrane and nuclear matrix, suggesting an association with the nucleo-cytoplasmic transport of ribonucleoproteins and the mechanisms of cell cycle and DNA replication, respectively. This study highlights the importance of alkaline phosphatase in the salivary gland of R. prolixus and R. neglectus and emphasizes its importance in secretory activity. Secretory activity is directly involved in hematophagy and, consequently, in development during metamorphosis. The observed presence of alkaline phosphatase suggests its involvement in the production of saliva allowing feeding of these insects that are important vectors of Chagas disease.
Keywords: Cytochemistry; Hematophagy; Triatominae subfamily